PENGARUH KEPEMIMPINAN KEPALA MADRASAH DAN KINERJA GURU TERHADAP MUTU MADRASAH - Abang Iwan (LP2M-PMP Universitas Siliwangi, 2019)
Madrasah quality is very dependent on the role of the madrasa head as educator, manager, administrator, supervisor, leader, innovator and entrepreneur in managing, managing, managing and empowering all available resources. In addition, the teacher also has a very vital role as an educator as a servant of the students, especially in the learning process starting from planning learning, implementing learning and evaluating / evaluating learning. The research problem is the influence of madrasa head leadership and teacher performance on madrasa quality. The research objectives to be achieved are to describe, measure and test the influence of madrasah head leadership and teacher performance on school quality. The formulation of the problem in this study is whether the leadership of the madrasah affects the quality of the madrasa, whether the performance of the teacher influences the quality of the madrasa and whether the leadership of the madrasa and the performance of the teacher together influence the quality of the madrasa. The population of this research is the 8 tasikmalaya state tsanawiyah madrasas in the Sariwangi District environment. The number of teachers is 45 people, a sample of 40 people is obtained by simple random sampling technique. The data collection method uses a questionnaire and documentation. Data analysis techniques using validity test, reliability test, classic assumption test, multiple linear regression, t test, and F test. To analyze research data using the SPSS for Windows Release 17 Program. From the results of this study it can be seen that the average acquisition of madrasah head leadership score of 123 which is included in the very good category, the average acquisition of teacher performance scores of 118.70 which is included in the very good category, the average acquisition of madrasah quality score of 128, 10 which is in the very good category. Prerequisite test results from the research data found no symptoms of multicollinearity, heteroscedasticity, and autocorrelation so that they were eligible to perform linear regression analysis. From the results of the hypothesis test, madrasa head leadership significantly influences the quality of madrasas with a t-test value of 7.116. Teacher performance has a significant effect on the quality of madrasas with a t-test value of 2.678. Madrasah headship leadership and teacher performance simultaneously have a significant effect on madrasa quality with an F-test score of 42,347. The contribution of madrasah head leadership and teacher performance to madrasa quality is 69.6%. Madrasa head leadership and teacher performance will greatly affect the quality of madrasas together. Even so madrasa must constantly evaluate themselves madrasa to meet the desires of customers who are constantly changing.